نحو نظام ضريبي فعال في الجزائر - طالبي, محمد; العقون, أم الخير (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الورقة البحثية إلى معالجة إشكالية كيفية الوصول إلى نظام ضريبي فعال في الجزائر من خلال التطرق إلى تطور وتقييم أداء النظام الضريبي الجزائري وبنيته بعد العديد من الإصلاحات التي انتهجتها الجزائر في ظل التطورات التي ظهرت على الساحة الدولية والمحلية، وللوصول إلى أهداف الدراسة تم استخدام المنهج الوصفي التحليلي. وقد توصل البحث إلى أن النظام الضريبي لايزال يعاني من مجموعة من التحديات والاختلالات التي تحد من فعاليته وتحول دون تحقيق الأهداف الاستراتيجية المتمثلة في إحلال الجباية العادية محل الجباية البترولية، لذلك لابد من وضع مقترحات لتحقيق الأهداف المرجوة منه وليصبح أكثر تكيفا مع المتغيرات التي يشهدها الاقتصاد العالمي، This research paper aims to address the problem of how to reach an effective tax system in algeria by addressing the development and evalution of the performance and structure of the Algerian tax system after many reforms adopted by Algeria in light of the developments that have emerged on the international and domestic arena, and to reach the objectives of the study, the method was used. Descriptive analytical. The research concluded that the tax system still suffers from a set of challenges and imbalances that limit its effectiveness and prevent the achievement of the strategic objectives represented in replacing oil levy with regular collection. Therefore, proposals must be developed to achieve the desired goals and to become more adaptive to the changes in the global economy.
Keywords: نظام الضريبي – الحصيلة الضريبية – الجباية العادية – الإصلاح الضريبي – الجزائر ; : tax system ; tax proceeds; regular collection ; tax reform ; Algeria